Studying the personal and social variables associated with the empowerment of Saudi women – A field study on a sample of women in the city of Al-Ahsa, Kingdom of Saudi Arabia - Alnaim, Luluh Abdulhamid (Journal of Humanities & Social Sciences, 2024)
Study problem: This study tries to clarify the reality of empowering Saudi women from their own point of view by studying the most prominent personal and social variables related to empowering Saudi women and the extent of their practice of empowerment and its reflection on improving their social, economic, and personal situation through the following main question: What are the most prominent personal and social variables associated with empowering Saudi women? Objectives: The study sought to identify the most prominent personal and social variables associated with the empowerment of Saudi women. Methodology: This study relied on a descriptive analytical study using the sample social survey approach. A social scale was built. It includes indicators of the dimensions of empowerment that included several axes: social variables that included social, economic, personal, and legal empowerment, and personal variables related to Saudi women such as level of education, age, and marital status) using purposive sampling (27) woman. Results: Results of the study revealed that the social variables represented in opening opportunities for women and amending legislation and laws related to women’s empowerment contributed profoundly to the awareness and practice of Saudi women in reality, as it was shown that there is awareness among women about empowerment at all legal, personal, economic and social levels. It turned out that the highest mean score for the dimensions of empowerment for Saudi women was in the personal dimension (8.9), then the legal dimension (8.5), followed by the social dimension (8.2), and finally the economic dimension (7.6).